TM-Chain: TCB Measurement Management Using Cloud Blockchain for IoT Devices - Jaemin Park; Sungjin Park (IEEE Access)
Remote attestation (RA) is a process for checking whether a device’s underlying Trusted Computing Base (TCB) and sensing data from the TCB are trustworthy. In the IoT era, RA is an important security feature because verifiers make critical decisions based on the RA result. However, a massive and diverse collection of measurements for IoT devices makes managing the devices’ TCB measurements difficult and complex. The cloud blockchain is a possible candidate for addressing the problem, but the tailored approach is essential to support scalable and secure management. We present a cloud blockchain-based management of the TCB measurements for IoT devices called TM-Chain (TCB Measurement-Chain). TM-Chain presents the TM-Chain transactions, commands, and protocols to manage the TCB measurements using the cloud blockchain. Based on TM-Chain, the verifiers launch remote attestation against the target devices using the TCB measurements verified by the cloud blockchain. We implemented a proof-of-concept (PoC) on a device to evaluate the performance overhead and a PoC on a public cloud to assess the feasibility.